Future directions for implementation science at the National Cancer Institute: Implementation Science Centers in Cancer Control. Issue 2 (7th March 2020) - Oh, April; Vinson, Cynthia A; Chambers, David A
Abstract: The National Cancer Institute (NCI) Cancer Moonshot initiative seeks to accelerate cancer research for the USA. One of the scientific priorities identified by the Moonshot's Blue Ribbon Panel (BRP) of scientific experts was the implementation of evidence-based approaches. In September 2019, the NCI launched the Implementation Science Centers in Cancer Control (ISC3 or "Centers") initiative to advance this Moonshot priority. The vision of the ISC3 is to promote the development of research centers to build capacity and research in high-priority areas of cancer control implementation science (e.g., scale-up and spread, sustainability and adaptation, and precision implementation), build implementation laboratories within community and clinical settings, improve the state of measurement and methods, and improve the adoption, implementation, and sustainment of evidence-based cancer control interventions. This paper highlights the research agenda, vision, and strategic direction for these Centers and encourages transdisciplinary scientists to learn more about opportunities to collaborate with these Centers.